Gendered Dimensions of Labor and Living Incomes Among Coffee Farmers in Southern Mexico - Lyon, Sarah; Mutersbaugh, Tad; Worthen, Holly (DIE ERDE – Journal of the Geographical Society of Berlin, 2024)
The Fairtrade Standard for Small-Scale Producer Organizations was recently adjusted to reflect core International Labour Organization (ILO) conventions on good working conditions. The standards require smallholders to offer permanent and temporary workers training on labor rights as well as gradual salary increases to close the gap between existing wages and living income targets. However, many smallholder coffee producers depend on inexpensive labor sources like wage laborers, household members, or other community members who engage in reciprocal or collective labor exchanges to meet quality demands and comply with certification standards. Coffee producers in southern Mexico face labor-intensive farm renovations, tight labor markets, and the advancing age (and declining size) of farm families. These shifting labor burdens have differential gender impacts, and farmers find it difficult to finance long-term farm investments at current Fairtrade prices. Thus, a living income—whether for farmers or laborers—remains a distant dream, not an achievable, short-term objective. Using data from nearly 500 smallholder coffee producers in Oaxaca, Mexico, this article explores i) how Fairtrade-certified smallholders manage the labor demands of coffee production and ii) how these practices are specifically gendered. We explore how smallholders meet labor demands and the rationales underpinning their methods, noting the constraints, opportunities, and why these labor practices matter for smallholders, their communities, and long-term Fair Trade supply chain resilience.